Pandangan Ekonomi Dan Kesadaran Lingkungan Petani Terhadap Penggunaan Varietas Padi MSP Di Kecamatan Kotabumi Utara - Putra, Ungki Prabowo; Lestari, Sri Puji; Sari, Yuni Elmita; Bakti, Aji Setiya; Nufus, Zakiatun; Atik, Yansen (Universitas Muhammadiyah Kotabumi, 2025)
Rice farming has received significant attention from the government, which aims to increase production. Problems that often occur in agriculture, especially rice farming, are unstable production and price uncertainty during the harvest season. Efforts have been made to minimize negative impacts economically and environmentally. One of the efforts made is by using MSP (Let's Prosper Farmers) rice varieties that have been certified as superior varieties. Economic perspectives and environmental awareness are important parts of agricultural sustainability. Sustainable agriculture, in addition to being profit-oriented, must also maintain the condition of the surrounding environment. North Kotabumi District is an area that has used the MSP rice variety. This study is expected to provide input and contribution to formulating appropriate strategies and policies to create a sustainable rice farming system, which is not only economically profitable but also environmentally friendly. The study was conducted in Talang Jali, Madukoro, and Wonomarto Villages in North Kotabumi District, North Lampung Regency. A total of 32 farmers became research respondents. The data collection technique used an interview technique using a Likert scale. Data analysis used qualitative descriptive. As many as 53.12% of farmers have a moderate category towards economic views in the use of MSP rice varieties. Farmers' environmental awareness is included in the high category with 59.37% of farmers having a positive perception of the environment.